Museums, sexuality, and gender activism - Adair, Joshua G.; Levin, Amy K., 1957- (London : Routledge, 2020)
Museums, Sexuality, and Gender Activism examines the role of exhibitionary institutions in representing LGBTQ+ people, cisgender women, and nonbinary individuals. Considering recent gender and sexuality-related developments through a critical lens, the volume contributes significantly to the growing body of activist writing on this topic. Building on Gender, Sexuality and Museums and featuring work from established voices, as well as newcomers, this volume offers risky and exciting articles from around the world. Chapters cover diverse topics, including transgender representation, erasure, and activism; two-spirit people, indigeneity, and museums; third genders; gender and sexuality in heritage sites and historic homes; temporary exhibitions on gender and sexuality; museum representations of HIV/AIDS; interventions to increase queer visibility and inclusion in galleries; LGBTQ+ staff alliances; and museums, gender ambiguity, and the disruption of binaries. Several chapters focus on areas outside the US and Europe, while others explore central topics through the perspectives of racial and ethnic minorities. Containing contributions that engage in sustained critique of current policies, theory, and practice, Museums, Sexuality, and Gender Activism is essential reading for those studying museums, women and gender, sexuality, culture, history, heritage, art, media, and anthropology. The book will also spark interest among museum practitioners, public archivists, and scholars researching related topics.
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Social aspects; Museums and women; Museums and sexual minorities; SOCIAL SCIENCE / Gender Studies; SOCIAL SCIENCE / Gay Studies